2018
DOI: 10.1017/sus.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Business experience of floods and drought-related water and electricity supply disruption in three cities in sub-Saharan Africa during the 2015/2016 El Niño

Abstract: Non-technical summaryThe El Niño event in 2015/2016 was one of the strongest since at least 1950. Through surveys and interviews with key informants, we found businesses in the capital cities of Zambia, Botswana and Kenya experienced major disruption to their activities from El Niño related hydroelectric load shedding, water supply disruption and flooding, respectively. Yet, during the 2015/2016 El Niño, fluctuations in precipitation were not extreme considering the strength of the El Niño event. Results there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…(iii) The extent to which such changes affect power generation and the actual capacity factor of hydropower plants depends on multiple factors, including: the direction and magnitude of the change; the type of dam in question; and for the case of reservoirs, the features and size of reservoir; among multipurpose dams (which are usually also the largest), the withdrawal from concurrent uses and thus the use of shared water resources in the region by the agricultural sector, the industry, and residential areas (Lee et al, 2009); and the transboundary basin management (Conway et al, 2015).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…(iii) The extent to which such changes affect power generation and the actual capacity factor of hydropower plants depends on multiple factors, including: the direction and magnitude of the change; the type of dam in question; and for the case of reservoirs, the features and size of reservoir; among multipurpose dams (which are usually also the largest), the withdrawal from concurrent uses and thus the use of shared water resources in the region by the agricultural sector, the industry, and residential areas (Lee et al, 2009); and the transboundary basin management (Conway et al, 2015).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In the last decades (in particular during the wet season in unimodal rainfall climates, where rain falls only during one period per year) prolonged droughts have resulted in severe power crises in several hydropower-dependent countries (including for instance, in Kenya, Tanzania, Ghana, Zimbabwe and Zambia during the 2015-16 El Niño period, characterized by oceanic and atmospheric shifts in the Pacific Ocean which affect weather and climate across the tropics, and in Malawi in 2017), with frequent outages, power rationing , adverse business experience (Gannon et al, 2018) to emergency (and costlier) IPP (independent power producer)-provided dieselfired generators . Water availability issues represent a growing source of risk in different areas, also due to an increasing competition between water use for power generation, irrigation, and municipal water supply (Zeng et al, 2017;.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Governments and development partners could, for example, support adaptation by domestic private businesses through providing credible and easily accessible scientific information, through weather and climate services, through guidelines, models, and tools and through cofinancing research and developing new products and services (Agrawala et al, ; Biagini & Miller, ; Crawford & Seidel, ; OECD, ; Stenek et al, ; United Nations Global Compact and UNEP, ). Surveys of SMEs in Gaborone, Lusaka and Nairobi, following the 2015–2016 El Niño, for example, illustrate the value of climate services, wherein 28% of SMEs surveyed noted that forecasts and other early warning systems helped their business to plan for El Niño associated water supply disruption, hydroelectric load shedding, and flooding (Gannon et al, ). In this study, business managers described attempting to limit disruption through ex ante changes to their business inventory, investment decisions, supply chains, and savings behavior; although notably other SMEs reported that other barriers to action limited the value of early warnings.…”
Section: Drivers and Barriers To Private Sector And Sme Adaptation—whmentioning
confidence: 99%
“…As a result, load sheddings, brownouts, and blackouts are recurrent. Over the recent years, drought-related disruptions have been reported, for instance, in Kenya, Malawi, Tanzania, Ghana, Zimbabwe and Zambia, with frequent outages, power rationing, adverse business experience and competitiveness loss during precipitation anomalies [11].…”
Section: Introductionmentioning
confidence: 99%